Analysis Use of PERT/CPM: Optimizing Manufacturing Production Process Resources for Building Construction Projects on Kunjang River Region, East Kalimantan - Prapdopo, Prapdopo; Ambalinggi, Yonal; Sriwahyuni, Linda; Norhidayanti, Siti; Oktavia, Fayza (Journal of Business Management and Economic Development, 2024)
This study discusses the application of the PERT (Program Evaluation and Review Technique) or CPM (Critical Path Method) in optimizing the manufacturing process of construction project resources in the Sungai Kunjang area, East Kalimantan. The objective of this study is to provide a holistic perspective on sustainable project management indicators that affect construction project processes. The focus is on identifying sustainable project management indicators that affect construction project processes. This study was conducted in the Sungai Kunjang area, which has high infrastructure development potential and requires effective project management to manage construction project resources. The expected outcome of this study is to help improve project performance and achieve sustainable development in the area.